Donación en la transformación. El nóema en Jean-Luc Marion - Paredes Gascón, Antonio (2020)
“Donation on the Transformation. Noema on Jean-Luc Marion”. Here we try to study Jean-Luc Marion’s treatment of the noema and, by extension, the noesis-noema correlation, which is basic for the understanding of the so-called “saturated phenomenon”. In order to do so, we think about such correlation in Husserl, with the aim to ultimately know its justification and to understand the final meaning it has in Husserl’s work, too. In addition, we discover the transformation operated in the noesis-noema structure by Lévinas and the “counterintentionality” of the Other, which will decisively influence on Marion, who expands that counter-intentionality —and the consequent questioning of the noesis-noema structure of intentionality in Husserl—to include every saturated phenomenon.